Parental stress and its associated factors among parents of autism spectrum disorder children in Kota Kinabalu Sabah - Razali, Ahmad Abdul Jalil Mohd (2017)
Background: Parenting an Autism Spectrum Disorder (ASD) children had been established to cause significant stress. Ascertaining its prevalence in local setting and identifying the predictors for parental stress could be an important step in formulating a practical intervention to avert a more disruptive psychological outcome. Objectives: The objective of this study was to establish the prevalence of parental stress among parents of ASD children, examine the factors associated with parental stress, and examine the association between ASD specific characteristic and parental stress. Methods: This was a cross-sectional study involving 103 parents with their ASD children attending the Child Intervention and Enrichment Centre (CIEC), Hospital Mesra Bukit Padang, Kota Kinabalu Sabah from August 2016 to October 2016. Parent’s whose child was diagnosed with ASD according to Diagnostic and Statistical Manual for Mental Disorder, fifth edition (DSM-5) and fulfilled the selection criteria were included in to the study. Parental stress was evaluated by means of Parental Stress Index-Short Form (PSISF). ASD children’s severity was rated using Childhood Autism Rating Scale (CARS). Sociodemographic characteristic for parents and their children were recorded in Participant’s Data Sheet. The prevalence of parental stress was established using the clinically significant cutoff score of PSI-SF (>90th percentile) while the association between sociodemographic characteristic, ASD severity, and ASD specific characteristic with parental stress were analysed using Multiple Linear Regression.Results: The prevalence of parental stress among parents of ASD children in CIEC, Kota Kinabalu was 39.8%. Factors associated with parental stress were mothers (B=16.82, p<0.001) and ASD severity (B=1.62, p<0.001). The ASD specific characteristic predictors for parental stress in the study were ‘object use’ and ‘intellectual response’. Conclusion: The prevalence of parental stress among ASD children’s parents in Kota Kinabalu were relatively low. Mothers experience significant parental stress as compared to fathers and ASD severity had a significant association with parental stress. ASD children with deficit in ‘object use’ and ‘intellectual response’ would predict significant stress in their parents. Intervention targeting at modifying these variables could improve parental stress.